Intermittent employment: Work histories of Israeli men and women, 1983-1995 - Shoshana Neuman; Adrian Ziderman (Bar-Ilan University, Department of Economics, 2009)
This study examines the extent, duration and timing of employment breaks amongst a large representative sample of Jewish workers in Israel over the 13-year time period, 1983-1995. Work histories are constructed from a new joint database, unique in Israel, which was derived from a linkage of 1995 Population Census data with monthly employment records of the National Insurance Institute. The paper focuses on gender differences in work history patterns and, within each gender, breakdowns are provided by ethnic origin, marital status, age, and education level. The main results are compatible with current economic theories of household behavior; yet some of the findings of the study are less expected, particularly those relating to the considerable amount of intermittent employment found amongst Israeli male workers. Also, women's labor market attachment is stronger than is generally presumed. Gender differences in employment interruptions are greater for younger than older workers.
Keywords: J2; J6; R2; 330; employment; gender; work histories; Israel